To demonstrate polynomial addition correctly, we need to add the corresponding terms of each polynomial.
Let's add the given polynomials in option B as an example:
- First polynomial: \(2x^2 + 6x + 1\)
- Second polynomial: \(3x^2 + 3x + 9\)
Now, let's add them term by term:
- For \(x^2\) terms: \(2x^2 + 3x^2 = 5x^2\)
- For \(x\) terms: \(6x + 3x = 9x\)
- For the constant terms: \(1 + 9 = 10\)
Putting it all together, we have:
\[ (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10 \]
Therefore, the correct option that demonstrates polynomial addition is:
D. (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10.